Self-Assembling β-Glucan Nanomedicine for the Delivery of siRNA - Lee, Kyungwoo (Biomedicines, 2020)
We aimed to design and manufacture a transporter capable of delivering small interfering RNAs (siRNAs) into the skin without causing any damage. β-glucans are unique chiral polysaccharides with well-defined immunological properties and supramolecular wrapping ability. However, the chiral properties of these polymers have hardly been applied in drug delivery systems. In this study, β-glucan nanoparticles were designed and manufactured to deliver genetic material to the target cells. The β-glucan molecules were self-assembled with an siRNA into nanoparticles of 300–400 nm in diameter via a conformational transition process, in order to construct a gene delivery system. The assembled gene nanocarriers were associated with high gene-loading ability. The expression and efficiency of siRNA were verified after its delivery via β-glucan. Our results provide evidence that β-glucan nanoparticles can be effectively used to deliver siRNA into the cells.